Systemic Anti-inflammatory Activity of American Cockroach (Periplaneta americana) Extract: A Molecular Docking Study - Aritonang, Erfan Andrianto; Gunanti; Purwono, Rini Madyastuti; Supriyono (Media Kedokteran Hewan, 2024)
Surgery can trigger systemic inflammatory response syndrome. This study aims to determine the effectiveness of Periplaneta americana cockroach extract as an oral systemic anti-inflammatory agent using molecular docking. The molecular docking method consisted of five steps. The first step was preparing the TNF-α converting enzyme (TACE) receptor as a native ligand, dexamethasone as a control ligand, and three test ligands of Periplaneta americana cockroach extract. The second step was docking preparation. The third step was analyzing Gibbs free energy (âˆ†G) and root mean square deviation (RMSD). The fourth step was docking the test and control ligands with TACE. The fifth step was analyzing âˆ†G, inhibition constant (Ki), visualization of two- and three-dimensional interactions, percentage of binding site similarity (%BSS), and the rule of five (Ro5) on test ligands. The âˆ†G results for the native, control, and test ligands 1, 2, and 3 were -12.8, -7.1, -7.7, -6.9, and -9.0 kcal/mol, respectively. The Ki values for the native, control, and test ligands 1, 2, and 3 were 4.091, 6.205, 2.253, 9.521, and 2.507 µM, respectively. The results of the Ro5 analysis suggested that the three test ligands satisfied Lipinski's rule of five. This study concluded that Periplaneta americana cockroach extract is an effective oral systemic anti-inflammatory agent.